MODEL IMPLEMENTASI PENYUSUNAN ANGGARAN BELANJA PADA SISTEM INFORMASI PEMERINTAHAN DAERAH DI KOTA BANDUNG - Iqbal Darmawan Sutisna; Septiana Dwiputrianti; Abdul Rahman (Journal Of Regional Public Administration (JRPA), 2022)
Regional financial management is a strategic issue whose regulations are regulated by the Central Government by issuing regulations including Government Regulation of the Republic of Indonesia Number 12 of 2019 concerning Regional Financial Management, Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems, and Ministerial Regulation Domestic Affairs Number 90 of 2019 concerning Classification, Codefication, and Nomenclature of Regional Development Planning and Finance, which was later refined by Decree of the Minister of Home Affairs Number 050-3708 of 2020 concerning Verification and Validation Results of Updating Classification, Codefication and Nomenclature of Regional Development Planning and Finance. The issuance of these new regulations has a significant impact on local governments, because the nomenclature of regional apparatus, programs and activities, as well as codification has changed significantly. This also has an impact on the financial management system used by local governments. As a result of the issuance of Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems, all regional governments in Indonesia are required to use the Regional Government Information System (SIPD) which is accessed through the official website of the Ministry of Home Affairs. With the lack of socialization and training obtained, the Bandung City Government needs to move quickly to anticipate the dynamics of this regulatory change, by intensifying communication with regional officials and providing assistance in each stage of financial management. In connection with the phenomenon of policy implementation regarding the model for preparing the budget in SIPD as the implementation of Permendagri 70 of 2019, the thinking model built in connection with this research uses a theoretical study from George C. Edwards III, which in the process uses several variables, namely: communication, resources, attitude of implementers, bureaucratic structure. In this study, the researcher provides recommendations, including optimizing socialization and technical guidance, intensifying coordination with various parties, improving the quality of human resources, compiling SOPs regarding regional financial management.